Oxidative stress does not play a primary role in the toxicity induced with clinical doses of doxorubicin in myocardial H9c2 cells - Rharass, Tareck; GBANKOTO, Adam; Canal, Christophe; Kursunluoğlu, Gizem; Bijoux, Amandine; RIBOU, ANNE-CECILE (My University, 2016)
The implication of oxidative stress as primary mechanism inducing doxorubicin (DOX) cardiotoxicity is still questionable as many in vitro studies implied supra-clinical drug doses or unreliable methodologies for reactive oxygen species (ROS) detection. The aim of this study was to clarify whether oxidative stress is involved in compliance with the conditions of clinical use of DOX, and using reliable tools for ROS detection. We examined the cytotoxic mechanisms of 2 μM DOX 1 day after the beginning of the treatment in differentiated H9c2 rat embryonic cardiac cells. Cells were exposed for 2 or 24 h with DOX to mimic a single chronic dosage or to favor accumulation, respectively. We found that apoptosis was prevalent in cells exposed for a short period with DOX: cells showed typical hallmarks as loss of anchorage ability, mitochondrial hyperpolarization followed by the collapse of mitochondrial activity, and nuclear condensation. Increasing the exposure period favored a shift to necrosis as the cells preferentially exhibited early DNA impairment and nuclear swelling. In either case, measuring the fluorescence lifetime of 1-pyrenebutyric acid or the intensities of dihydroethidium or amplex red showed a consistent pattern in ROS production which was a slight increased level far from representative of an oxidative stress. Moreover, pre-treatment with dexrazoxane provided a cytoprotective effect although it failed to detoxify ROS. Our data support that oxidative stress is unlikely to be the primary mechanism of DOX cardiac toxicity in vitro.
Keywords: Apotosis-Cardiotoxicity-Dexrazoxane-Doxorubicin-Necrosis-Oxidative stress